Activation of CD3+ T cells by Helicobacter pylori DNA vaccines in potential immunotherapy of gastric carcinoma. Issue 6 (3rd June 2019) - Xue, Li-Jun; Mao, Xiao-Bei; Liu, Xiao-Bei; Gao, Han; Chen, Ya-Nan; Dai, Ting-Ting; Shao, Sheng-Wen; Chen, Hong-Min; Chu, Xiao-Yuan
ABSTRACT: Most of gastric carcinoma (GC) is attributed to infection by Helicobacter pylori ( H. pylori ) but there is increasing evidence that the positive H. pylori status correlates with better prognosis in GC. The H. pylori -induced cellular immune response may suppress cancer and in this work, recombinant pcDNA3 plasmids encoding various fragments of H. pylori virulence genes of cag A, vac A and bab A are constructed and combined into groups to immunize BALB/c mice. The activated splenic CD3 + T cells are purified and the anticancer effects are investigated in vitro and in vivo . The H. pylori DNA vaccines induce a shift in the response from Th1 to Th2 that mimicks the immune status in patients of GC with chronic H. pylori infection. The stimulated CD3 + T cells inhibit the growth of human GC cells in vitro and adoptive transfusions of the CD3 + T cells suppress the growth of GC xenograft in vivo . The effects may be caused by the larger ratios of infiltrated CD8 + /CD4 + T cells, reduced infiltration of regulatory FOXP3 + T cells, and enhanced apoptosis induced by upregulation of Caspase-9/Caspase-3 and downregulation of Survivin. Our results reveal the potential immunotherapeutic value of H. pylori vaccine-activated CD3 + T cells in those with advanced GC.